2004
DOI: 10.1002/ijc.20188
|View full text |Cite
|
Sign up to set email alerts
|

Irradiated C6 glioma cells induce angiogenesis in vivo and activate endothelial cells in vitro

Abstract: Malignant gliomas are angiogenesis dependent and present a remarkable degree of resistance to radiotherapy. In the present work, we studied the effect of irradiation of C6 glioma cells on their proliferation and activation in vitro and on glioma cell-induced angiogenesis in vivo and in vitro. Irradiation of C6 glioma cells decreased cell proliferation in a dosedependent manner. Interestingly, metalloproteinase-2 and -9 expression and secretion, as well as integrin ␣ v expression, increased with elevated doses … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
20
0
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 34 publications
(38 reference statements)
4
20
0
1
Order By: Relevance
“…In accordance with earlier studies [20], [24]–[25], the present data showed that X-ray radiation enhanced the secretion of VEGF , a potent angiogenic growth factor [26], as well as that of MMP - 2 and - 9 , which degrade the basement membrane and extracellular matrix during tumor cell invasion and metastasis [27]. In contrast, VEGF and MMP - 2 and - 9 levels were not significantly increased by carbon ion radiation; indeed, VEGF secretion was reduced at 4.0 Gy (Fig.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…In accordance with earlier studies [20], [24]–[25], the present data showed that X-ray radiation enhanced the secretion of VEGF , a potent angiogenic growth factor [26], as well as that of MMP - 2 and - 9 , which degrade the basement membrane and extracellular matrix during tumor cell invasion and metastasis [27]. In contrast, VEGF and MMP - 2 and - 9 levels were not significantly increased by carbon ion radiation; indeed, VEGF secretion was reduced at 4.0 Gy (Fig.…”
Section: Discussionsupporting
confidence: 94%
“…Carbon ion radiation has been shown to suppress migration and the formation of capillary-like tube structures in ECV304 and human umbilical vascular endothelial cells at a dose of 0.1 Gy [19]. In contrast, conditioned media from tumor cells exposed to X-ray radiation stimulated cell migration and tube formation, consistent with previous findings [20]. The migration and invasion of glioma cells into surrounding normal brain tissue and blood vessels contributes to the limited responsiveness of gliomas to conventional radiation treatments [21][22].…”
Section: Discussionsupporting
confidence: 87%
“…The authors noticed a dose dependent vacuolization of endothelial cells as well as growth retardation, resulting in a remarkable reduction in the vascular endpoint density. Finally, several preclinical studies in the CAM have used combination therapy and demonstrated an increased effectiveness when radiotherapy is combined with an anti-angiogenic treatment [156,157]. …”
Section: Cam As a Screening Platformmentioning
confidence: 99%
“…Malignant glioma cells are inherently chemo- [161] and radioresistant [162]. Also, as radiation of glioma cells may potentiate the expression of proangiogenic molecules [163], combining radiotherapy with antiangiogenic therapy may also prove to be clinically useful and effective. By way of the CSC vascular niche hypothesis, the future of therapeutic strategy will continue to require a multidimensional approach to tumor eradication.…”
Section: Antiangiogenic Therapymentioning
confidence: 99%